A technical-pedagogical and historical reflection on the conceptual and biomechanical properties of Ko-do-kan ju-do-'s "ko-uchi-gari" (minor inner reaping throw) - de Crée, C.; Edmonds, D. A. (Comprehensive Psychology, 2012)
Throwing techniques represent an important part of Ko-do-kan ju-do-, aimed at defeating an opponent. Ko-uchi-gari [minor inner reaping throw] is a versatile throw of which the exact origin is unknown. Clear and correct ju-do--specific and didactic terminology are helpful in acquiring the complex motor skills that enable a refined and highly technical ju-do-. Ko-uchi-gari relies on the physics principle of a "simple couple," i.e., an acting pair of two bound opposing forces around the opponent's center of mass with the result, in this case, being perpendicular to those forces, hence producing a torque. Appreciating this may provide an idea about the method this throwing technique is relying on to achieve its success and about its challenges. The purpose of the present paper is to improve the understanding of ko-uchi-gari from a historical, terminological, linguistic, technical, and biomechanical perspective in order to facilitate transferring or acquiring the motor skills necessary to properly master and teach this ju-do- throwing technique.